IJTIHAD ULAMA DALAM MERUMUSKAN METODE MEMAHAMI MAQÂSID AL-SYARÎ’AH - Saende, Zubair Rahman; Sultan, Lomba; Syatar, Abdul (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2023)
This paper is intended to find a method of understanding maqâsid al-syarî'ah in Ijtihad of Islamic law. The method used is literature review using descriptive analysis. The study in this writing demonstrates that the method of understanding maqâsid al- syarî'ah has four forms of approach taken by experts, namely (1) lafziyah, (2) maknawiyah (3) meaning outside the text using Istihsân and Istislah (Maslahah al- Mursalah) and (4) lafziyah and meaning. While there are also contemporary thinkers who develop methods of understanding maqâsid al-syarî'ah with the term al-adillah al-syar'iyyah al-maqâsid al-syarî'ah iyyah divided into two methods: (1) al-adillah al-syar'iyyah al-maqâsid al-syarî'ah iyyah the development of al-adillah al-syar'iyyah ushul fiqh. (2) al-adillah al-syar'iyyah al-maqâsid al-syarî'ah iyyah excluding al- adillah al-syar'iyyah ushul fiqh. The urgency of this study is to create welfare, peace and happiness for humanity both in this world and in the hereafter and to answer problems in Islamic lawwhich do not find its law in the Qur'an and Sunnah.